On enzymatic remodeling of IgG glycosylation; unique tools with broad applications. (16th October 2019) - Sjögren, Jonathan; Lood, Rolf; Nägeli, Andreas
Abstract: The importance of IgG glycosylation has been known for many years not only by scientists in glycobiology but also by human pathogens that have evolved specific enzymes to modify these glycans with fundamental impact on IgG function. The rise of IgG as a major therapeutic scaffold for many cancer and immunological indications combined with the availability of unique enzymes acting specifically on IgG Fc-glycans have spurred a range of applications to study this important post-translational modification on IgG. This review article introduces why the IgG glycans are of distinguished interest, gives a background on the unique enzymatic tools available to study the IgG glycans and finally presents an overview of applications utilizing these enzymes for various modifications of the IgG glycans. The applications covered include site-specific glycan transglycosylation and conjugation, analytical workflows for monoclonal antibodies and serum diagnostics. Additionally, the review looks ahead and discusses the importance of O-glycosylation for IgG3, Fc-fusion proteins and other new formats of biopharmaceuticals.